2014
DOI: 10.3390/nu6093624
|View full text |Cite
|
Sign up to set email alerts
|

Fatty Acid Status and Its Relationship to Cognitive Decline and Homocysteine Levels in the Elderly

Abstract: Polyunsaturated fatty acids (PUFAs), especially the n-3 series, are known for their protective effects. Considering that cardiovascular diseases are risk factors for dementia, which is common at aging, the aim of this study was to evaluate whether fatty acid status in the elderly was associated with cognitive function and cardiovascular risk. Forty-five elderly persons (age ≥60 years) were included and divided into two groups based on their Mini-Mental Status Examination score adjusted for educational level: t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(30 citation statements)
references
References 47 publications
0
23
0
1
Order By: Relevance
“…A multitude of epidemiological studies have suggested that a diet rich in saturated free fatty acids (sFFA) adversely affects cognition [18, 19] and is closely associated with cognitive decline [20]. Also, the degree of saturated fat or saturated fatty acid intake in diet commensurately dictates the degree and extent of cognitive decline [21].…”
Section: Introductionmentioning
confidence: 99%
“…A multitude of epidemiological studies have suggested that a diet rich in saturated free fatty acids (sFFA) adversely affects cognition [18, 19] and is closely associated with cognitive decline [20]. Also, the degree of saturated fat or saturated fatty acid intake in diet commensurately dictates the degree and extent of cognitive decline [21].…”
Section: Introductionmentioning
confidence: 99%
“…[39] [40] [41]. Moreover the brain has high energy requirements, since this cerebral orange represents only 2% of the total body mass, consumes 20% of the oxygen and 25% of the glucose consumed by the total human body[42].The brain is a complex organ with high metabolism which by aging becomes more vulnerable to oxidative stress.…”
mentioning
confidence: 99%
“…In 2014, an observational case-control study by Baierle and colleagues enrolling 12 elderly patients with cognitive decline according to the mini-mental state examination (MMSE) performance test, showed lower levels of serum DHA and total n-3 PUFAs compared to 33 control patients with normal MMSE scores [83]. Cognitive functions were positively associated with DHA and total n-3 PUFAs levels.…”
Section: Latest Insight and Implications For Cognitive Performance Anmentioning
confidence: 99%